The Effectiveness of Antibiotics and Hematopoietic Stem Cell Treatment in Periodontitis Rat Model Toward TNF α Expression - R, Retno Indrawati; Diyatri, Indeswati; Rahmawati, Dwi (KnE Life Sciences, 2017)
Periodontitis is a biofilm-induced chronic inflammatory. The current therapy of periodontitis is scaling root planning and curettage, and followed by administration of antibiotic such as combination of Amoxicillin and Clavulanic acid. Hematopoietic Stem Cell has ability to differentiate into blood cells which is capable of homing and regenerating itself. Research Purpose: The aim of this study was to prove antibiotic and Hematopoietic Stem Cell administration can reduce TNF α expression. Method: This research was divided into four different groups, P1 as negative control group, P2 as positive control group which inoculated with P.gingivalis 109 for three weeks as chronic periodontitis rat model and USP were administered, P3 as chronic periodontitis rat model received Hematopoietic Stem Cell injection into the tail vein of rat, P4 as chronic periodontitis rat models were given Amoxicillin and Clavulanic acid 250 mg/kg BW orally then followed by Hematopoietic Stem Cell 106 injection into the tail vein of rat. After two weeks rat were sacrified and immunohistochemically analysed for expression of TNF α. The data were analysed by using Non-Parametric Test. Result: TNF α expression of negative control group was different as compared to positive control group and treatment group which given Hematopoietic Stem Cell injection, but there is no difference between negative control group with treatment group which given Amoxicillin and Clavulanic acid 250 mg/kg BW orally and followed by Hematopoietic Stem Cell injection. Clonclusion: The administration of Amoxicillin and Clavulanic acid 250 mg/kg BW and Hematopoietic Stem Cell can reduce TNF α expression on periodontitis rat model. Keyword: Hematopoetic Stem Cell, TNF α, Chronic Periodontitis, Antibiotic